2019
DOI: 10.1128/mbio.01942-19
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the Ankyrin H Core Effector of Legionella with the Host LARP7 Component of the 7SK snRNP Complex

Abstract: Species of the Legionella genus encode at least 18,000 effector proteins that are translocated through the Dot/Icm type IVB translocation system into macrophages and protist hosts to enable intracellular growth. Eight effectors, including ankyrin H (AnkH), are common to all Legionella species. The AnkH effector is also present in Coxiella and Rickettsiella. To date, no pathogenic effectors have ever been described that directly interfere with host cell transcription. We determined that the host nuclear protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 104 publications
0
48
0
Order By: Relevance
“…It was observed that a mutation of the third beta-hairpin loop in the ankyrin repeat domain abrogates binding of AnkH to LARP7 and leads to an intracellular growth defect of L. pneumophila. Taken together, these findings suggest that AnkH-mediated transcriptional reprogramming is essential for infection (61).…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…It was observed that a mutation of the third beta-hairpin loop in the ankyrin repeat domain abrogates binding of AnkH to LARP7 and leads to an intracellular growth defect of L. pneumophila. Taken together, these findings suggest that AnkH-mediated transcriptional reprogramming is essential for infection (61).…”
mentioning
confidence: 63%
“…The AnkH-LARP7 interaction partially impedes interaction of LARP7 with the 7SK snRNP complex components, thus interfering with transcriptional elongation by RNA polymerase II. As a consequence, AnkH-dependent global transcriptional reprogramming of the host cell promotes intracellular bacterial growth (61). The N-terminal domain of AnkH contains four ankyrin repeats with a typical structural fold of two alpha-helices, forming a helix-turn-helix motif, joined by a beta-hairpin loop.…”
mentioning
confidence: 99%
“…In L. pneumophila, the AnkH effector has recently been shown to interact with the host nuclear protein LARP7, which is a component of the 7SK small nuclear ribonucleoprotein (snRNP) complex. The AnkH-LARP7 interaction interferes with transcriptional elongation by RNA Pol II, leading to the global reprogramming of transcription of infected macrophages and contributing to the proliferation of Legionella [102] (Figure 2A). Legionella nucleomodulin SnlP illustrates another way to control RNA Pol II.…”
Section: Ever More Substrates and Functions: An Expanding Familymentioning
confidence: 99%
“…In addition to ANK repeats, there have also been two asparagine hydroxylation motifs identified within AnkH [179]. The crystal structure of AnkH has revealed two Asn hydroxylation motifs, four ANK domains, as well as a cysteine-like protease domain and a CAP domain [188]. We have previously shown that two of the ANK domains are required for proper function of the protein, since deletion of either domain results in an intracellular replication defect [185].…”
Section: Structure Of Ankh and Its Role In The Intracellular Survivalmentioning
confidence: 99%
“…One of the ANK domain containing effector proteins, AnkH, has been shown to be required for intracellular replication of L. pneumophila in amoebae, human macrophages, and for intrapulmonary proliferation in the mouse model of infection. The crystal structure revealed that AnkH consists of four ANK domains, a cysteine-like protease domain, two asparagine hydroxylation motifs, and a cap domain [188]. The Legionella genus codes for ~18,000 effector proteins.…”
Section: Figure 1-2: Ankh Is Not Involved In Lcv Formation or Evasionmentioning
confidence: 99%